2020
DOI: 10.1186/s13047-020-00434-8
|View full text |Cite
|
Sign up to set email alerts
|

´Feet are second class citizens': exploring the perceptions of Scottish and Portuguese older adults about feet, falls and exercise‐ a qualitative study

Abstract: Introduction Foot problems are likely to contribute to falls risk in older adults. Foot and ankle exercises may be beneficial, but uptake may be influenced by cultural factors. Few studies have explored the views of older adults from different cultural backgrounds about foot-specific falls risk factors, and foot and ankle falls prevention exercises. Objectives To explore the views of Scottish and Portuguese community-dwelling older adults who have experienced a fall, about any foot risk factors for falls, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…It was important to ascertain physiotherapists' views about their older patients' knowledge in their nation as a qualitative study found that British and Portuguese older adults' consider that health professional's (including physiotherapists) messages to them about foot health, footcare, exercise and falls prevention are of the utmost importance for informing their knowledge and preventive behaviours (Conde et al., 2020). Both the UK‐based and Portugal‐based physiotherapists perceived that their older clients had little knowledge about footcare, foot‐specific fall risk factors, or foot and ankle exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was important to ascertain physiotherapists' views about their older patients' knowledge in their nation as a qualitative study found that British and Portuguese older adults' consider that health professional's (including physiotherapists) messages to them about foot health, footcare, exercise and falls prevention are of the utmost importance for informing their knowledge and preventive behaviours (Conde et al., 2020). Both the UK‐based and Portugal‐based physiotherapists perceived that their older clients had little knowledge about footcare, foot‐specific fall risk factors, or foot and ankle exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having a very different professional scope landscape, Portugal has published an action plan for Physiotherapy in falls prevention in primary care settings (Barbosa et al, 2020). Since UK guidance and practice informed the Portuguese falls action plan (Barbosa et al, 2020) and a qualitative study pointed that British and Portuguese older adults 'knowledge and preventive behaviours regarding these topics were influenced by healthcare professionals' messages (including physiotherapists) (Conde et al, 2020), comparing physiotherapists from both nations seems relevant and timely. Hence, the main aim of this study was to compare selfreported knowledge, confidence, and practice surrounding general and foot-specific falls risk, exercise for falls prevention among physiotherapists working in the UK and in Portugal.…”
Section: Introductionmentioning
confidence: 99%